Solve for x: 2 over 3 (x - 4) = 2x.

Question

Asked 3/6/2014 12:18:00 PM

Updated 3/6/2014 10:31:01 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [3/6/2014 10:28:36 PM]

f(x) = 4^2(2) - 100

f(x) = 16(2) - 100

f(x) = 32 - 100

f(x) = -68

f(x) = 4^2(2) - 100

f(x) = 16(2) - 100

f(x) = 32 - 100

f(x) = -68

Question

Asked 3/6/2014 12:18:00 PM

Updated 3/6/2014 10:31:01 PM

1 Answer/Comment

This conversation has been flagged as incorrect.

Flagged by yeswey [3/6/2014 10:28:36 PM]

Rating

3

2/3 (x - 4) = 2x

multiply 3 on both sides we get 2(x - 4) = 6x

2x - 8 = 6x

4x = -8

x = -2

multiply 3 on both sides we get 2(x - 4) = 6x

2x - 8 = 6x

4x = -8

x = -2

Added 3/6/2014 10:31:01 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [3/7/2014 8:52:48 AM]

What value for y makes the sentence true?
5 - y = 5 - 3 User: Select the expression below that is equal to 5(9 - m).

Question

Expert Answered

Updated 3/6/2014 2:36:03 PM

3 Answers/Comments

5 - y = 5 - 3,

-y = 2 - 5

-y = -3

y = 3

-y = 2 - 5

-y = -3

y = 3

Added 3/6/2014 2:35:01 PM

This answer has been confirmed as correct and helpful.

jerry06, for inequality or equations, it's important to always show the solution to your answer, especially that it's added on the archives. It will be more useful to visitors.

Added 3/6/2014 2:36:03 PM

27,935,291

questions answered

There are no comments.